Assessing bank competition for consumer loans - Bolt, Wilko; Humphrey, David (Journal of Banking & Finance, 2015)
Based on frontier analysis, we derive inferences of bank consumer loan competition from estimating a revenue-cost ‘competition efficiency’ (CE) frontier. The competitiveness of the $400 billion U.S. bank consumer loan market is then assessed by comparing results from our frontier CE measure with other competition measures, such as HHI, Lerner Index, and H-Statistic. These measures are weakly related to one another and only half of them identify banks with the highest loan price as also being the least competitive. This is the opposite of what is expected. Using the frontier CE measure, the most and least competitive banks are not located in the most populous states and the largest banks are underrepresented. Overall, the HHI should not be used to indicate competition.